PENGARUH DANA PIHAK KETIGA (DPK), CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), NET INTEREST MARGIN (NIM), DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP PENYALURAN KREDIT - Sudimoro Family, Syafira Tauhida Qulby (Contemporary Studies in Economic, Finance and Banking, 2023)
Banking is an important part that plays a role in the economic development of a country. Banking also functions as an intermediary institutions whose job is to collect funds from the public and channel them back to the community in the form of credit. In extending credit, there are internal factors that must be considered, namely the activities of banks collecting public funds are indicated by the amount of DPK, from the capital side it is indicated by CAR, the level of collectibility is indicated by NPL, the level of bank operational efficiency is indicated by NIM, and from a banking liquidity perspective indicated by LDR. This study aims to determine the effect of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR) on bank lending listed on the Stock Exchange. Indonesian securities for the 2012-2021 period using the purposive sampling method. The analytical method uses panel data regression. The results showed that DPK, CAR, NIM, and LDR had a positive and significant effect on lending. Meanwhile, NPL has a significant negative effect on lending. Keywords: Lending, DPK, CAR, NPL, NIM, LDR